2003
DOI: 10.1017/s0031182002002810
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic analysis of Tunisian Theileria annulata clones

Abstract: Many parasite species are known to show high levels of genetic diversity, yet the consequences of this diversity for host-parasite interactions are not well understood. Variation in phenotypic traits such as growth rates and the ability to form transmission stages are raw material for natural and artificial selection to act upon with consequences for the evolution of the parasite species and disease control. In order to study genetic and phenotypic diversity amongst Theileria annulata parasites, a collection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Not only do our results suggest that competitive suppression is genotype-specific and that levels of strain-transcending and strain-specific immunity depend on the exact clones infecting the host, we have even demonstrated that competitive hierarchies can be completely reversed depending on which clone infects the host first. Interestingly, such a mosaic of competitive interactions and reversal of competitive dominance could explain why in many diseases (e.g., Chotivanich et al 2000;Nevils et al 2000;Taylor et al 2003) virulence polymorphisms are maintained (Mackinnon and Read 2004). They indeed suggest that, contrary to theoretical expectations, avirulent parasites may play a larger role in nature than we have up till now granted them.…”
Section: Discussionmentioning
confidence: 90%
“…Not only do our results suggest that competitive suppression is genotype-specific and that levels of strain-transcending and strain-specific immunity depend on the exact clones infecting the host, we have even demonstrated that competitive hierarchies can be completely reversed depending on which clone infects the host first. Interestingly, such a mosaic of competitive interactions and reversal of competitive dominance could explain why in many diseases (e.g., Chotivanich et al 2000;Nevils et al 2000;Taylor et al 2003) virulence polymorphisms are maintained (Mackinnon and Read 2004). They indeed suggest that, contrary to theoretical expectations, avirulent parasites may play a larger role in nature than we have up till now granted them.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, the multiclonal character of T . annulata isolates collected from such clinical cases [ 26 27 ], prompted us to clone the isolates by limiting dilution which allowed us to analyse a greater number of sequences and to identify a larger number of mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Stock cultures of the four clones were maintained separately in exponential growth in RPMI medium (Brown 1987;Taylor et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The four clones were different parasite genotypes (based on polymerase chain reaction/restriction fragment length polymorphism and monoclonal antibody analysis) cultured in host cells from the same cow (Taylor et al 2003). Stock cultures of the four clones were maintained separately in exponential growth in RPMI medium (Brown 1987;Taylor et al 2003).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation